Creation of Applications Introduction to Moment Preparation An Earthquake Occurred Using Actionscrip 3.0 - Khairullah Khairullah; Alam Kurnia Hadi; Muntahanah Muntahanah; Eka Sahputra (Penerbit Jurnal Indonesia, 2023)
Indonesia is an archipelagic country which is geographically located at the confluence of four tectonic plates, namely the Indo-Australian, Eurasian and Pacific plates. In the southern part of Indonesia there is a volcanic belt in the form of volcanic mountains. Indonesia is one of the countries that has the highest level of seismicity in the world. The purpose of this study is to apply ActionScript 3 in making multiplatform applications to identify earthquake preparedness which can add insight to users in dealing with earthquake disasters, as a learning tool for children aged 8 to 12 years. This application is made using Adobe Flash Professional CS 6 software, ActionScript 3 as the programming language and Adobe Audition CS 6 as the supporting software. It is hoped that with this application users will be able to recognize earthquake learning. From the results of the research that has been done, it can be concluded that a multiplatform application to identify preparation for an earthquake has been successfully created which consists of 5 menus on the main menu, namely, about earthquakes, actions when an earthquake occurs, after an earthquake.